2023
DOI: 10.1093/jas/skad120
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of dimethyl itaconate protects against chronic heat stress-induced growth performance impairment and lipid metabolism disorder in broiler chickens

Abstract: This study aimed to investigate the protective effects of dietary supplementation of dimethyl itaconate (DI) on chronic heat stress (HS)-induced impairment of the growth performance and lipid metabolism in broiler chickens. 21 days old male Ross 308 broiler chickens (a total of 120, about 700 g body weight) were randomly divided into five treatment groups, including control group, HS group, HS + 50 mg/kg DI group, HS + 150 mg/kg DI group, and HS + 200 mg/kg DI group, and each group contains eight cages of twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…When the liver is damaged, the normal structure of liver cells is disrupted, leading to a significant increase in ALT and AST levels in the blood. In poultry, elevated levels of LDL-C indicate disturbances in lipid metabolism, which may contribute to the occurrence of metabolic-related diseases [47] ; HDL-C, as it aids in the removal of LDL-C from the body and transports it to the liver for metabolism, is generally considered "good cholesterol" [48] . In this study, we observed that the AST concentration was significantly lower in the LRFI group than in the HRFI group, while the HDL-C content was significantly higher in the LRFI group.…”
Section: Discussionmentioning
confidence: 99%
“…When the liver is damaged, the normal structure of liver cells is disrupted, leading to a significant increase in ALT and AST levels in the blood. In poultry, elevated levels of LDL-C indicate disturbances in lipid metabolism, which may contribute to the occurrence of metabolic-related diseases [47] ; HDL-C, as it aids in the removal of LDL-C from the body and transports it to the liver for metabolism, is generally considered "good cholesterol" [48] . In this study, we observed that the AST concentration was significantly lower in the LRFI group than in the HRFI group, while the HDL-C content was significantly higher in the LRFI group.…”
Section: Discussionmentioning
confidence: 99%
“…Broilers under heat stress usually suffered from an energy supply deficit due to their decreased feed intake and increased output for survival [ 19 ]. Numerous studies indicated that heat stress had detrimental effects on lipid utilization by reducing lipolytic capacity, enhancing TG transports from the liver to extrahepatic tissues and abdominal adiposity [ 4 , 5 , 19 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional management, especially feed additives, which exerts lipid-lowering, anti-oxidant, and/or anti-inflammatory effects, might represent a beneficial regulator to alleviate heat-stress-induced hepatic lipid metabolism disorders. For instance, itaconate and astaxanthin, which exert an anti-oxidant and anti-inflammatory capacity, were used to alleviate heat-stress-induced hepatic lipid metabolism disorders in broilers [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chronic HS increases the hepatic index (weight and liver enzymes), abdominal fat, lipid accumulation, thereby reducing the availability of nutrition for growth and development ( Oladeinde et al, 2023 ). This feature was explained by ( Li et al, 2023a ), who found that HS induces up-regulation of fat synthesis genes and down regulated lipolysis-related genes in broiler.…”
Section: Introductionmentioning
confidence: 90%
“…It is well established that HS is a significant environmental factor responsible for liver damage. Therefore, the elevation of TNF-α levels in the liver or serum may contribute to liver dysfunction ( Li et al, 2023a ).…”
Section: Introductionmentioning
confidence: 99%